Avaliação do fator de ajuste dinâmico presente nos métodos de localização MCLA e WCL - Tahara, David (Universidade Federal de São Carlos, 2022)
The revolution and importance of geolocalization technologies involving satellite signals has increasingly, in recent decades, extended to indoor environments. In this environments, GPS systems have signal attenuation, due to physical barriers and, consenquently, malfunction or no functioning. The internal location needs are broad and range from locating people in hospitals, from the firefighter in a burning environment, to the industry to locate parts or raw materials in the manufacturing environment. So, technologies that solve problems of localization in internal environments arise, being quite common nowadays the localization based on the received signal strength, due to the low implementation cost and simplicity. The localization process involves trilateration algorithms for position estimation. Two of these methods are the Modified Centroid Localization Algorithm (MCLA) and Weighted Centroid Localization (WCL) which in their optimized forms have a dynamic adjustment factor to improve accuracy. This work consists of evaluating the dynamic adjustment through computer simulation on two fronts: the first is an extensive search for the dynamic adjustment factor that minimizes the average error of the evaluated set of points; the second also searches extensively, but for adjustment factors that minimize the point-to-point error. A comparison is made between the results, together with the result of a value of dynamic adjustment found at literature. The simulations were satisfactory and the methodology presented allowed the average error to be smaller in all application cases.
Evaluation of the dynamic adjustment factor present in the MCLA and WCL localization methods
Keywords: Estimativa de posição 2D; Received Signal Strength Indicator; MCLA; WCL; OUTROS::ENGENHARIA MECATRONICA